Comparison of the Balance Accelerometer Measure and Balance Error Scoring System in Adolescent Concussions in Sports. (June 2013) - Furman, Gabriel R.; Lin, Chia-Cheng; Bellanca, Jennica L.; Marchetti, Gregory F.; Collins, Michael W.; Whitney, Susan L.
Background: High-technology methods demonstrate that balance problems may persist up to 30 days after a concussion, whereas with low-technology methods such as the Balance Error Scoring System (BESS), performance becomes normal after only 3 days based on previously published studies in collegiate and high school athletes. Purpose: To compare the National Institutes of Health's Balance Accelerometer Measure (BAM) with the BESS regarding the ability to detect differences in postural sway between adolescents with sports concussions and age-matched controls. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: Forty-three patients with concussions and 27 control participants were tested with the standard BAM protocol, while sway was quantified using the normalized path length (mG/s) of pelvic accelerations in the anterior-posterior direction. The BESS was scored by experts using video recordings. Results: The BAM was not able to discriminate between healthy and concussed adolescents, whereas the BESS, especially the tandem stance conditions, was good at discriminating between healthy and concussed adolescents. A total BESS score of 21 or more errors optimally identified patients in the acute concussion group versus healthy participants at 60% sensitivity and 82% specificity. Conclusion: The BAM is not as effective as the BESS in identifying abnormal postural control in adolescents with sports concussions. The BESS, a simple and economical method of assessing postural control, was effective in discriminating between young adults with acute concussions and young healthy people, suggesting that the test has value in the assessment of acute concussions.